Oczekiwania zagranicznych studentów względem polskich bibliotek. Na przykładzie studentów z Wietnamu - Wiorogórska, Zuzanna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
This paper presents partial results of the qualitative study conducted among Vietnamese students at the University of Warsaw. The study was about information competences and information literacy of this group as well as about their expectations towards Polish academic libraries. An in-depth structured interview was applied to collect data. Interviews were conducted in English. In the first part of the paper, I present the review of international literature on Asian students, in the context of their use of library services; I also discuss the Polish literature of this field. The core part of the paper presents the study results. The paper finishes with study findings and recommendations for academic libraries.